2024
DOI: 10.1001/jamanetworkopen.2024.0582
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Harm Perceptions of E-Cigarettes vs Cigarettes Among Adults Who Smoke in England, 2014-2023

Sarah E. Jackson,
Harry Tattan-Birch,
Katherine East
et al.

Abstract: ImportanceElectronic cigarettes (e-cigarettes) are less harmful to users than combustible cigarettes. However, public health and media reporting have often overstated the potential risks of e-cigarettes, and inaccurate perceptions of the harms of vaping relative to smoking are pervasive.ObjectiveTo examine time trends in harm perceptions of e-cigarettes compared with combustible cigarettes among adults who smoke.Design, Setting, and ParticipantsThis nationally representative monthly cross-sectional survey stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Roughly 3,000 cases and 68 deaths were reported across the U.S. from EVALI [14]. This new respiratory illness diagnosis associated with vaping supports the need for this study to explore if individuals who vaped experienced worsened COVID-19 presentations [15] or if the potential risks of e-cigarettes are overstated [16]. While uncertainty remains regarding the correlation between vapers and worsened COVID-19 presentations [18], calls for concerns by health professionals in 2022 led the Australian government to propose stronger regulation and enforcement of all e-cigarettes with an allocated budget of $63 million set for public health information campaigns to discourage Australians from taking up vaping, as well as smoking traditional tobacco cigarettes [19].…”
Section: Introductionmentioning
confidence: 81%
“…Roughly 3,000 cases and 68 deaths were reported across the U.S. from EVALI [14]. This new respiratory illness diagnosis associated with vaping supports the need for this study to explore if individuals who vaped experienced worsened COVID-19 presentations [15] or if the potential risks of e-cigarettes are overstated [16]. While uncertainty remains regarding the correlation between vapers and worsened COVID-19 presentations [18], calls for concerns by health professionals in 2022 led the Australian government to propose stronger regulation and enforcement of all e-cigarettes with an allocated budget of $63 million set for public health information campaigns to discourage Australians from taking up vaping, as well as smoking traditional tobacco cigarettes [19].…”
Section: Introductionmentioning
confidence: 81%
“…Fewer smokers in England now see vaping as less harmful than smoking cigarettes, despite evidence that tobacco is far worse for health, showed a survey of 28 000 smokers from 2014 to 2023 6. The latest round of results found that 57% thought vaping at least as harmful as smoking,7 in data published in JAMA Network Open and based on a weekly survey funded by Cancer Research UK.…”
Section: Vapingmentioning
confidence: 99%
“…Regarding other chemicals in e-cigarette aerosol, there is now a large body of evidence showing that they pose only a small fraction of the risks of smoking [7]. Regarding public misinformation and confusion, in sharp contrast to evidence, 57% of smokers in England believe that vaping is as harmful as or more harmful than smoking [8]. Bush et al [1] support this opinion when they state that vaping in pregnancy may or may not be the lesser of evils.…”
mentioning
confidence: 99%